The Impact of Head Room Leadership Style on Motivation and Performance of Implementing Nurses (A Literature Review - Leni Agustin; Siti Riskika; Hamidah Retno Wardani (D'Nursing and Health Journal (DNHJ), 2023)
Introduction: In nursing, leadership is the use of the skills of a leader (nurse) in influencing other nurses who are under his supervision for the division of tasks and responsibilities in providing nursing care services so that nursing goals are achieved (Latif, 2008). Leadership behavior will be reflected in the leadership style that appears when leading his subordinates. In influencing the performance of subordinates, an effective leadership style is needed. The purpose of this study is to review some of the literature that contains the leadership style of the head of the room that can improve and optimize the motivation and performance of nurses in hospitals as an effort to improve the quality of nursing services. Method: Literature search strategy through Google schoolar using several keywords, namely "headroom leadership style", "nurse performance", "nurse work motivation". Literature search is limited from December 2010 to December 2014. Literature search from 1 database found 10 articles and then selected and reviewed, only 3 articles were found that matched the inclusion criteria set by the author. The inclusion criteria in this review is the leadership style of the head of the room that affects the motivation & performance of nurses in hospitals. Result: The results of the research from the 3 articles there is a positive influence between the leadership style of the head of the room with the motivation and performance of nurses that can improve the quality of nursing services and improve overall organizational performance. Conclusion: The leadership style of the ward head can increase the motivation & performance of nurses in providing nursing care.